Effect of mannan oligosaccharides on the performance, intestinal morphology and cecal fermentation of fattening rabbits (2013)
The five experimental treatments were as follow: Control (no additives); MOS 1 (Bio-Mos®, 1 g kg−1); MOS 1.5 (Bio-Mos®, 1.5 g kg−1); MOS 2 (Bio-Mos®, 2 g kg−1) and AGP (Zn-Bacitracin; 0.1 g kg−1). Experimental diets were based on alfalfa, sunflower meal, wheat and beet pulp and were offered ad libitum through out the experiment. Trial 1 used 400 weaned mixed-sex rabbits divided into the five treatments with 10 replicates and 8 rabbits/replicate. Rabbits were weighed at weaning (day 32) and at the end of the experiment (day 67). Weight gain, feed intake, feed conversion ratio (FCR) and mortality were evaluated using a commercial grow-out facility. Trial 2 used 220 weaned rabbits divided into the same five experimental treatment groups and housed in groups of 4 in 11 flat deck cages located in an experimental rabbit house. In trial 2 performance, intestinal morphology and cecal fermentation were determined. In both trials, rabbit daily weight gain and feed intake were not affected by treatments. However, in trial 1 MOS rabbits had better (P<0.05) FCR than control rabbits and similar to AGP rabbits. Also in this trial, the mortality with MOS and AGP treatments tended to be lower (P=0.052) than with control diet. Results in trial 2 showed longer villi (P<0.05) in rabbits fed MOS or AGP compared to the control group, this resulted in increased absorption surface. Cecal volatile fatty acid (VFA) concentration differed (P<0.05) between treatments. Rabbits fed MOS at 1 g kg−1 had higher total VFA concentration compared to the Control as well as the AGP treatment. Furthermore, cecal pH was significantly lower in rabbits fed MOS at 1 and 2 g kg−1 compared to the control. A reduction on total bacterial count in ileum contents (P<0.05) and Coliforms and Enterococci in cecal contents with MOS supplementation of diet was observed. Results for these studies showed that the addition of MOS resulted in similar performance compared to an antibiotic growth promoter. Furthermore, differences in mortality, intestinal morphology and cecal VFA concentration suggest that MOS can improve the health status of growing rabbits.